Self-Medication-Induced Exanthematous Drug Eruption in A 19-Year-Old Male with Uncomplicated Gonococcal Urethritis - Ersi Dwi Utami Siregar; Redha Cipta Utama (International Journal of Science and Society, 2026)
Improper self-medication, especially with antibiotics, continues to be a major cause of skin reactions to drugs. Unprotected sexual activity in young adults elevates the risk of sexually transmitted infections, including gonococcal urethritis, which may be exacerbated by inappropriate antibiotic usage. A 19-year-old male presented with a two-day history of pruritic erythematous eruptions involving the trunk. The patient had self-administered cotrimoxazole 480 mg for purulent urethral discharge and dysuria prior to presentation. He reported his first sexual encounter with a commercial sex worker following peer influence, without condom, and disclosed a background of family instability. Dermatological examination revealed multiple erythematous macules on the chest, abdomen, and back. Venereological examination demonstrated mild erythema of the external urethral meatus with mucopurulent discharge. Microscopic examination of urethral secretions identified intracellular gram-negative diplococci. A diagnosis of exanthematous-type allergic drug eruption secondary to cotrimoxazole and non-complicated gonococcal urethritis was established. The patient was treated with a single intramuscular dose of ceftriaxone 250 mg, a single oral dose of azithromycin 1 g, and intravenous dexamethasone 5 mg three times daily for three days. Marked clinical improvement was observed after four days of hospitalization, with resolution of cutaneous lesions and negative follow-up urethral smear. This case underscores the dermatological and venereological consequences of antibiotic misuse in young adults and highlights the importance of early recognition of drug eruptions, appropriate antimicrobial therapy, and comprehensive sexual history assessment.